2013
DOI: 10.1016/j.jpeds.2012.11.062
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Evaluation of Children with and without Shwachman-Bodian-Diamond Syndrome Gene Mutations and Shwachman-Diamond Syndrome

Abstract: Objective To characterize the endocrine phenotype of patients with Shwachman-Diamond syndrome (SDS). Study design Clinically indicated endocrine screening data from 43 patients with SDS or SDS-like presentation were analyzed according to sex, age, and genetic testing. In addition to 25 patients with biallelic Shwachman-Bodian-Diamond syndrome (SBDS) gene mutations, we evaluated 18 patients with cytopenias who were receiving pancreatic enzyme replacement but were without SBDS mutation. We performed a retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Patient 05 is still receiving growth hormone treatment, while patients 01 and 07 received the treatment around puberty with moderate response. Four similar cases have been previously reported . Transaminasemia was documented in 55% of the patients but resolved during follow‐up in all but one patient .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Patient 05 is still receiving growth hormone treatment, while patients 01 and 07 received the treatment around puberty with moderate response. Four similar cases have been previously reported . Transaminasemia was documented in 55% of the patients but resolved during follow‐up in all but one patient .…”
Section: Discussionsupporting
confidence: 77%
“…Four similar cases have been previously reported. [13][14][15] Transaminasemia was documented in 55% of the patients but resolved during follow-up in all but one patient. 3,16 Consistent to previous reports, mild cognitive impairment was recorded in four patients.…”
Section: Discussionmentioning
confidence: 96%
“…Although short stature and failure to thrive are not included in diagnostic criteria of SDS, most papers [2,5,[12][13][14][15][16] and our data indicate that abnormal somatic development comprises a cardinal symptom of the syndrome. It is common for most patients.…”
Section: Discussionmentioning
confidence: 71%
“…There is a significant variability in clinical phenotype, even within families. Most studies on the somatic development of children with SDS have been limited to weight and height, with only a few studies assessing BMI [5,[12][13][14][15][16]. The majority of studies demonstrated that SDS patients present with growth failure, nevertheless systematic data concerning those features are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, hematopoietic stem cell transplantation is reported to be the only effective method to treat bone marrow failure [9]. In addition, growth hormone therapy can have the benefits of SDS with short stature [10]. Based on the GH stimulation test results, the child was treated with rhGH, and the therapeutic effect is satisfactory.…”
Section: Discussionmentioning
confidence: 99%